2019
DOI: 10.1177/1742395319843163
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender and race on heart failure self-care

Abstract: Objectives To explore gender and racial differences in heart failure (HF) self-care processes and examine whether gender and race predict HF self-care. Methods A secondary analysis of baseline data ( n = 107) from a longitudinal HF study (54.2% males; 56% non-Caucasians) was conducted. The self-care of heart failure index was used to measure self-care maintenance, management, and confidence. Descriptive statistics and univariate analyses examined gender and racial differences in HF self-care outcomes. Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
4
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
5
4
1
3
Order By: Relevance
“…In this study, race was significantly associated with self-care maintenance in both bivariate and multiple regression analysis (controlling for education and marital status). This finding differs from those of Graven et al (2019) who found no statistically significant association between race and self-care maintenance. We know that not only are racial minorities disproportionately burdened by poor health and that they are also more likely to live in geographical areas with poor SDH (Virani et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, race was significantly associated with self-care maintenance in both bivariate and multiple regression analysis (controlling for education and marital status). This finding differs from those of Graven et al (2019) who found no statistically significant association between race and self-care maintenance. We know that not only are racial minorities disproportionately burdened by poor health and that they are also more likely to live in geographical areas with poor SDH (Virani et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…The mean scores obtained for each section of the SCHFI were below 70 points, meaning that the participants presented a non-appropriate self-care behaviour. These findings are in accordance with other studies [12,14,[27][28][29][30][31]. However, the mean values in those studies were higher, ranging from 50 to 65 points, in contrast with the ones from the present study, which ranged between 35 and 45.…”
Section: Self-care Behavioursupporting
confidence: 92%
“…In a study with Brazilian patients similar results were found related to the differences in self-care maintenance [27]. Contrarily to our results, in the study of Graven et al, NYHA class II patients present higher levels of self-care behaviour, in absolute values, even though they were not statistically significant [29].…”
Section: Pathophysiological Characteristicssupporting
confidence: 89%
See 2 more Smart Citations